2019
DOI: 10.1016/j.anireprosci.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile of milk for determining reproductive status in lactating Holstein Friesian cows

Abstract: Large percentages of dairy cows do not express behavioural signs of oestrus. Faecal and urine fatty acid concentrations increase during oestrus. The objective of the present study was to determine the milk FA profile of dairy cows during the oestrous and dioestrous periods and the relationship with behavioural signs on the day of oestrus. The activity of 32 Holstein Friesian cows was measured continuously using GEA Rescounter ll pedometers (GEA Farm Technologies, Düsseldorf, Germany) and IceQubes (IceRobotics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…It is known that short-chain fatty acids such as acetic-, propanoic-and butyric acid, are relatively abundant due to bacterial fermentation in colonic lumen which regulate entero-pathogenic colonization by host immunomodulation in human (Smith et al 2013;Wrigley 2004). A recent study shows that acetic, valeric, caproic and myristoleic acids are at signi cantly higher levels in the milk of estrus cow (Zebari et al 2019). The fatty acids, acetic and propanoic, have been identi ed in the faeces of cow, and varied in relation to the time of ovulation (Mozūraitis et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that short-chain fatty acids such as acetic-, propanoic-and butyric acid, are relatively abundant due to bacterial fermentation in colonic lumen which regulate entero-pathogenic colonization by host immunomodulation in human (Smith et al 2013;Wrigley 2004). A recent study shows that acetic, valeric, caproic and myristoleic acids are at signi cantly higher levels in the milk of estrus cow (Zebari et al 2019). The fatty acids, acetic and propanoic, have been identi ed in the faeces of cow, and varied in relation to the time of ovulation (Mozūraitis et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that milk composition alters with the occurrence of estrus [ 8 , 9 , 10 ]. Importantly, the present study indicated that the days in relation to estrus had a significant effect on many infrared wavenumbers.…”
Section: Possible Use Of Milk Mir Spectra In the Reproductive Managementmentioning
confidence: 99%
“…Specific fatty acids, such as myristic acid and palmitic acid, decreased from proestrus to estrus with a concomitant increase in stearic acid and oleic acid. Zebari et al [ 9 ] found that the concentration of acetic acid, valeric acid, caproic acid, and myristoleic were greater in milk on the day of estrus compared to the diestrus period, whereas the milk arachidonic acid concentration was greater in the diestrus period compared to the day of estrus. Zhao et al [ 10 ] showed that inactive-ovary cows compared with normal-estrus cows at 70 days postpartum had an increase in the milk whey of six different metabolites, including succinate, creatine phosphate, glycine, myo-inositol, glycolate, and orotate, and a decrease in the milk whey of seven metabolites, including alanine, creatinine, o-phosphorylcholine, lactose, taurine, galactose, and glucose-1-phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…Octanoic acid is a saturated fatty acid present in natural food sources, such as coconut, palm kernel and milk [ 10 ]. It exhibits antibacterial activity against various species, including S. aureus , Escherichia coli and Candida albicans [ [11] , [12] , [13] , [14] , [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%